Lithiation and Substitution of N′-(ω-Phenylalkyl)-N,N-dimethylureas - Smith, Keith; El-Hiti, Gamal A.; Alshammari, Mohammed B. (Synthesis, 2012)
Lithiation of N′-phenethyl-N,N-dimethylurea with three equivalents of tert-butyllithium in anhydrous tetrahydrofuran at –78 °C takes place on the nitrogen and on the side-chain of the CH2 next to the phenyl ring (α-lithiation). The 2-lithio isomer can be obtained via bromine–lithium exchange of N′-2-(2-bromophenyl)ethyl-N,N-dimethylurea using methyllithium followed by tert-butyllithium in tetrahydrofuran at –78 °C. The lithium reagents thus obtained react with various electrophiles to give the corresponding substituted derivatives in excellent yields. Lithiation of N′-(3-phenylpropyl)-N,N-dimethylurea takes place on the α-CH2 with tert-butyllithium at 0 °C. On the other hand, lithiation of N′-(4-phenylbutyl)-N,N-dimethylurea with tert-butyllithium at 0 °C takes place on one of the methyl groups of the urea unit.
Keywords: N′-phenethyl-N,N-dimethylurea; side-chain lithiation; bromine–lithium exchange; electrophile; synthesis